The Use Of Augmented Reality (AR) In Accounting Education: A Bibliometric Analysis - Chozin, Chozin; Sunariyadi, Sunariyadi; Sukarsih, Sukarsih; Handayati, Puji; Restuningdiah, Nurika (PT. EQUATOR SINAR AKADEMIA, 2025)
The use of Augmented Reality (AR) in accounting education is becoming increasingly important with the development of technology now. This study aims to reveal trends over the past ten years with bibliometric analysis to examine the results of articles related to the use of AR in accounting education. This study collected articles from the Scopus database from 2015 to 2025, using the Scopus Web analysis feature and visualizing the bibliometric network using VOSviewer. A total of 100 articles were accessed through various filtering processes. This study distributes the results based on publication year and most researched articles. The results found that AR has proven effective in improving accounting students' conceptual understanding and practical skills, especially in difficult materials such as accounting cycles and financial statements. AR technology facilitates visual, interactive, and contextualized learning. The implication of this study is the need for special training for educators to optimize the use of AR in accounting education.